Resolución del agrandamiento gingival mediante terapia periodontal no quirúrgica: reporte de caso - Soriano Angulo, Rafael (2016)
ABSTRACT: Gingival enlargement is a chronic inflammatory lesion caused by bacterial plaque. It appears as a tumefaction at the level of the inter-dental papilla and/or marginal gingival tissue; it can be localized or generalized. It exhibits slow and painless progression and can be exacerbated by hormonal causes or use of drugs. The present article studies the case of a patient afﬂicted with gingival enlargement and gingival lesions induced by bacterial plaque. The case was resolved with use of non surgical periodontal therapy. For seven days, antibiotic therapy and manual therapy were conducted. Re-evaluation one month later revealed resolution of the enlargement, decrease of inﬂammation, suppuration, periodontal pocket percentage and degree of dental mobility; periodontal maintenance was executed at that point. After three months, decrease of periodontal pockets percentage and degree of dental mobility were observed; at that point maintenance periodontal therapy was conducted.